2022
DOI: 10.2298/tsci200524348a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of using graphene nanoplatelets and hybrid nanofluid as coolant in photovoltaic thermal systems

Abstract: It is a common observation that the photovoltaic (PV) panelshows a compromised performance when its temperature rises. To handle the performance reduction, most PV panels are equipped with a thermal absorber for removing the solar cells? excessive heatwith the help of a heat transfer fluid. The mentioned thermal absorber system is termed as PV thermal or simply PV/T. This study aims to experimentally investigate the effectsof a graphene nano-platelets (GNP) nanofluid, distilled water, and hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The nanofibers with a periodic unsmooth surface are potentially of great technological interest for the development of solar energy absorption, and their other applications include invisibility devices, electronic sensors, applied surface science, photonics, physics, microelectronics, nanomaterials, advanced textile, photothermo-promoted nanocatalysis, photothermal semiconduction, photoactivatable cancer immunotherapy, and environmental science ( Li et al, 2019 ; Li X. et al, 2021 ; Li J. et al, 2021 ; Yang et al, 2021 ). We anticipate that this article will be a starting point for more sophisticated studies of intelligent nanomaterials for solar energy harvesting for solar cells ( Pavlovic et al, 2021 ; Alshikhi and Kayfeci 2022 ) or solar collector systems ( Al-Rabeeah et al, 2022 ). The periodic structure of nanomaterials via bioinspiration for energy gives many promises and great challenges ( Gong et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The nanofibers with a periodic unsmooth surface are potentially of great technological interest for the development of solar energy absorption, and their other applications include invisibility devices, electronic sensors, applied surface science, photonics, physics, microelectronics, nanomaterials, advanced textile, photothermo-promoted nanocatalysis, photothermal semiconduction, photoactivatable cancer immunotherapy, and environmental science ( Li et al, 2019 ; Li X. et al, 2021 ; Li J. et al, 2021 ; Yang et al, 2021 ). We anticipate that this article will be a starting point for more sophisticated studies of intelligent nanomaterials for solar energy harvesting for solar cells ( Pavlovic et al, 2021 ; Alshikhi and Kayfeci 2022 ) or solar collector systems ( Al-Rabeeah et al, 2022 ). The periodic structure of nanomaterials via bioinspiration for energy gives many promises and great challenges ( Gong et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was later found that metal oxide nanoparticles were cheaper and had conductivity similar to the original set. Carbon nanotubes have also been used for nanofluids, as they have unique thermal properties and superior thermal capabilities. These nanotubes come in two types, single-walled and multiwalled, and can have diameters ranging from one nanometer to several nanometers with a cylinder length of several micrometers . Their thermal conductivity (2000–6000 W/m 2 K) is much higher than that of the metallic or metal oxide nanoparticles. Nanofluids made up of carbon nanotubes can disperse and raise the thermal conductivity of the base fluid .…”
Section: Introductionmentioning
confidence: 99%
“…18−20 These nanotubes come in two types, single-walled and multiwalled, and can have diameters ranging from one nanometer to several nanometers with a cylinder length of several micrometers. 21 Their thermal conductivity (2000− 6000 W/m 2 K) is much higher than that of the metallic or metal oxide nanoparticles. 22−24 Nanofluids made up of carbon nanotubes can disperse and raise the thermal conductivity of the base fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene, due to its outstanding properties, has the widest range of applications (including electronics, optics [1], photovoltaics [2], spintronics [3], etc.). One of its fascinating fields of application is its use as a basis for the creation of new 2D materials.…”
Section: Introductionmentioning
confidence: 99%